2012
DOI: 10.1016/j.ijfoodmicro.2011.10.013
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative approach towards a better understanding of the dynamics of Salmonella spp. in a pork slaughter-line

Abstract: 26Pork contributes significantly to the public health disease burden caused by Salmonella

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 22 publications
2
54
0
2
Order By: Relevance
“…In addition, identification of specific serotypes (Table 3) in ABF carcass and processing plant environmental samples, which were not detected at the farm level, suggests the role of the slaughter environment as a source for cross-contamination. Identification of serotypes, including S. Agona, S. Braenderup, S. Derby, S. Inverness, S. Muenchen, and S. Newport, which were not found in farm and slaughter environments on ABF carcass (Table 3) is attributed to the slaughter robots, including the carcass splitter and other instruments used for processing the carcass as a possible source of contamination during the production chain as described previously (39). We observed some common serotypes in the ABF and conventional production systems, including S. Anatum, S. Infantis, and S. Typhimurium.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, identification of specific serotypes (Table 3) in ABF carcass and processing plant environmental samples, which were not detected at the farm level, suggests the role of the slaughter environment as a source for cross-contamination. Identification of serotypes, including S. Agona, S. Braenderup, S. Derby, S. Inverness, S. Muenchen, and S. Newport, which were not found in farm and slaughter environments on ABF carcass (Table 3) is attributed to the slaughter robots, including the carcass splitter and other instruments used for processing the carcass as a possible source of contamination during the production chain as described previously (39). We observed some common serotypes in the ABF and conventional production systems, including S. Anatum, S. Infantis, and S. Typhimurium.…”
Section: Discussionmentioning
confidence: 99%
“…In industrialized countries, meat samples, if contaminated, often harbor very low numbers of Salmonella (11,12); therefore, an enrichment step is an inevitable part of molecular detection methods. Ideally, this enrichment should maximize the number of Salmonella organisms while limiting the background flora.…”
mentioning
confidence: 99%
“…Omitting the time-consuming enrich-ment step would therefore be optimal, and several direct detection methods have also been published (9,(18)(19)(20). However, most of these methods are complex, not high throughput, and have detection limits of Ͼ50 CFU/25 g, i.e., above the reported levels of Salmonella in meat (12). Moreover, the legislative demand of absence of 1 CFU/25 g (21) cannot currently be met by the available direct detection technologies, making some sort of short-culture enrichment step necessary.…”
mentioning
confidence: 99%
“…Numerous studies have identified S. Rissen in slaughtered pigs in Portugal [4] and within pig fattening units and from slaughter-age pigs and Spain [5] [6] [7] [8] [9]. There have been further reports of S. Rissen in pig abattoir studies in Italy [10], Belgium [11], the Netherlands [12], Portugal [13] as well as in breeding herds in the UK [14] and in finishing pigs in Northern Ireland [15], thus demonstrating its' increase in European pig herds.…”
Section: Introductionmentioning
confidence: 99%